Bronchial brushings for investigating airway inflammation and remodelling - Looi, K.; Sutanto, E.; Banerjee, B.; Garratt, L.; Ling, K.; Foo, C.; Stick, S.; Kicic, Anthony (Wiley-Blackwell Publishing Asia, 2011)
Asthma is the commonest medical cause for hospital admission for children in Australia, affects more than 300 million people worldwide, and is incurable, severe in large number and refractory to treatment in many. However, there have been no new significant treatments despite intense research and billions of dollars. The advancement in our understanding in this disease has been limited due to its heterogeneity, genetic complexity and has severely been hampered particularly in children by the difficulty in obtaining relevant target organ tissue. This review attempts to provide an overview of the currently used and recently developed/adapted techniques used to obtain lung tissue with specific reference to the airway epithelium. Â© 2011 The Authors Respirology Â© 2011 Asian Pacific Society of Respirology.